2005
DOI: 10.1007/s10508-005-1006-8
|View full text |Cite
|
Sign up to set email alerts
|

Family Size in White Gay and Heterosexual Men

Abstract: There is some evidence for a genetic influence on sexual orientation. However, gay men have fewer children than heterosexual men. Increased fecundity in the biological relatives of gay men could offset this selection pressure. We measured family size in gay (n = 301) and heterosexual (n = 404) men, attending clinics for sexually transmitted infections. The main outcome measure was the number of each man's uncles and aunts, first cousins, siblings, nephews and nieces, and his own children. With the exception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 10 publications
(6 reference statements)
10
101
7
1
Order By: Relevance
“…It should be noted, however, that other investigators have reported a generalized fecundity increase in other members in the pedigrees of male HS probands, independent of the maternal or paternal line (King et al 2005;Schwartz et al 2010), and Rieger et al (2012), based on the dataset by Schwartz et al (2010), found excess fecundity in brothers of male HS. Subsequently, the data by Schwartz et al (2010) were reanalyzed by Camperio Ciani and Pellizzari (2012), highlighting, also in this dataset, a previously unnoticed larger maternal-line female fecundity.…”
Section: Human Homosexualitymentioning
confidence: 80%
“…It should be noted, however, that other investigators have reported a generalized fecundity increase in other members in the pedigrees of male HS probands, independent of the maternal or paternal line (King et al 2005;Schwartz et al 2010), and Rieger et al (2012), based on the dataset by Schwartz et al (2010), found excess fecundity in brothers of male HS. Subsequently, the data by Schwartz et al (2010) were reanalyzed by Camperio Ciani and Pellizzari (2012), highlighting, also in this dataset, a previously unnoticed larger maternal-line female fecundity.…”
Section: Human Homosexualitymentioning
confidence: 80%
“…Another study found the same pattern for aunts in a sample of white men in England-but the pattern was reversed in nonwhites and extended to more categories of relatives and in both sexes (Rahman et al 2008). A second study in England found more relatives for homosexual compared to heterosexual men on the paternal side of the family lineage and the same but nearly significant pattern (P ϭ 0.058) on the maternal side of the family (King et al 2005). Another study found that homosexual men have more siblings (of both sexes) compared to a sample of heterosexual men (Blanchard and Lippa 2007).…”
mentioning
confidence: 85%
“…Studies examining the degree to which monozygotic, dizygotic and adopted siblings share their sexual orientation indicate that the tendency to be gay or lesbian is heritable and can run in families [40], and might confer a reproductive fitness advantage to the relatives of gay men [50][51][52][53]. However, such studies are limited in their ability to elucidate the genetic architecture of traits such as sexual orientation.…”
Section: Box 2 Insights From Studies Of Human Homosexual Orientationmentioning
confidence: 99%